Differential diagnosis of small round cell tumours (SRCT), fluorescence in situ hybridization (FISH) and immunohistochemical (IHC) study - Ptaszyński, Konrad; Szumera-Ciećkiewicz, Anna; Pękul, Monika; Nowecki, Zbigniew (Polish Journal of Pathology, 2009)
Introduction: Small round cell tumours (SRCT) of bone and soft tissue constitute a heterogeneous group of neoplasms with similar histological and cytological features. Immunohistochemical studies with panels of antibodies are necessary in order to make the diagnosis. A molecular testing is helpful in many cases. Aim of the study: To assess the value of IHC and FISH tests in the differential diagnosis of SRCT. Material and methods: The material was obtained from patients diagnosed and treated at the Maria Skłodowska-Curie Memorial Cancer Center-Institute in Warsaw between February 2003 and March 2009. One hundred and thirty one patients with the initial diagnosis of SRCT of bone or soft tissue were qualified to the investigation. The material from the primary tumour was obtained by an open or core biopsy in all the patients. During the treatment the patients were monitored, the local recurrence and the distant metastases were reported. The IHC study was performed routinely using wide panels of antibodies. FISH tests: EWSR1, SS18 (SYT), FKHR (FOXO1A) and FUS were carried out using dual colour, break-apart probes. Results: IHC tests for CD99 and FLI-1 showed low specificity, had low sensitivity, myogenin staining revealed high specificity and sensitivity. A “lymphoma” panel with LCA, CD20, CD79a, TdT, CD3 showed acceptable specificity and sensitivity. There were 28 (21.37%) uninformative FISH results showing no acceptable signals. Conclusions: Diagnostic assessment of SRCT requires IHC studies as an introductory method. FISH is necessary in many cases of SRCT for the final diagnosis but it requires well-fixed and processed tissue, otherwise there is a high percentage of uninformative results. A diagnostic algorithm including IHC and FISH tests has been proposed.